THE CATEGORIES AND PLOTINIAN AESTHETICS - Schroeder, Frederic (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2020)
Aristotle regards the informed particular as primary substance and real. Plotinus as a Platonist sees intelligible substance as real and the particulars that belong to a genus as secondary substance and ontically deficient. To avoid the infinite regress involved in predicating the Form both of the particular and the Form Aristotle locates the Form in the particular. Plotinus preserves the transcendence of Form by replacing the Aristotelian predication by synonymy with a system of predication built on pros hen equivocity. The Form then becomes eidos aneideon, “formless form.” This formless form is, not a restricted entity, but rather as an ocean of possibity. As such it dismisses the world of Aristotelian science and opens up new possibilities for understanding art. The Form is regarded as an individual aspect of the intelligible world which is expressed in a P-series which extends from the intelligible world to sensible reality.